Prevalence of Metabolic Syndrome in Acute Myocardial Infarction Patiens in Bangladeshi Population - Khan, MMR; Rahman, MK; Sana, NK; Uddin, M Rais; Khan, MAL; Islam, M Monir Ul; Haque, M Zahirul; Basak, PM; Sarker, BC; Mohanta, DK; Das, Chinmoy Kanti (TAJ: Journal of Teachers Association, 2018)
This was a hospital based study done to see the prevalence of metabolic syndrome in acute myocardial infarction patients in Bangladesh. A total of 325 acute myocardial infarction patients attending in coronary care unit Rajshahi medical college hospital were included in this study. According to modified NCEP ATP III criteria 48.5% of subjects aged ≥ 20 years had the metabolic syndrome and it was more commonly seen in women than in men (72% vs 37.4%). The metabolic syndrome is associated with an increased risk of acute myocardial syndrome. TAJ 2011; 24(2): 82-84